2010
DOI: 10.26719/2010.16.1.101
|View full text |Cite
|
Sign up to set email alerts
|

<An> analysis of carbon monoxide poisoning cases in Bursa, Turkey

Abstract: from 1996 to 2006. Of 305 patients treated over a 10-year period, only 1 case was recorded as suicide. The CO source was a coal heater in 85.9% of cases. Mean Glasgow coma score (GCS) on admission was 12.8 (SD 0.2) and mean carboxyhaemoglobin level was 21.6% (SD 0.92%). There were statistically significant associations between higher GCS score, older age and higher HbCO level. Better education of the public is vital for the prevention of these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 7 publications
3
23
0
5
Order By: Relevance
“…Especially in the winter months, leaks from coal heaters are the major instruments of deaths (15,16). Data from Bursa, Turkey for the period between 1996 and 2006 showed that coal heater emissions were the source in 86% of CO poisoning cases (7). The present study found that 92% of fatal CO poisonings were Dec: December, Jan: January Dec: December caused by wood or coal heaters.…”
Section: Figure4 Fatal Carbon Monoxide Poisoning Due To Monthsmentioning
confidence: 72%
See 2 more Smart Citations
“…Especially in the winter months, leaks from coal heaters are the major instruments of deaths (15,16). Data from Bursa, Turkey for the period between 1996 and 2006 showed that coal heater emissions were the source in 86% of CO poisoning cases (7). The present study found that 92% of fatal CO poisonings were Dec: December, Jan: January Dec: December caused by wood or coal heaters.…”
Section: Figure4 Fatal Carbon Monoxide Poisoning Due To Monthsmentioning
confidence: 72%
“…CO poisoning therefore is a serious health threat on a global level. Most of poisoning deaths caused by accidental CO poisoning can be prevented with simple prevention measures (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çalışmamızda vakaların hepsi kaza sonucu zehirlenmişti. Ülkemizde CO zehirlenmesi ile ilgili yapılmış ça-lışmaların bazılarında en sık saptanan CO kaynağının şofben (%68.3-%77.5) olduğu bildirilmişken (16,17) bazı çalışmalarda da soba (%85.9-%89.7) olduğu bildirilmiştir (15,18). Çalışma-mızda zehirlenmelere en sık neden olan CO kaynağının soba (%82.1) olduğu bulundu.…”
Section: Bulgularunclassified
“…Çalışmamızda Kasım-Aralık-Ocak aylarında CO zehirlenmesi oranı toplam %89.3 olarak bulunurken, daha önce ülkemizde yapılmış olan çalışmalarda aynı aylarda bu oran %38.9-%64.6 arasında bulunmuştur (4,16,18). Mendoza ve ark.…”
Section: Tablo 4 Klinik Değerlendirmeye Göre Tedavi Süreleri Dağılımıunclassified